O Investimento estrangeiro e as atividades públicas: regime jurídico doméstico e contribuições da OCDE e OMC na regulação e contratação administrativas - Coêlho, Carolina Reis Jatobá (2021)
The aim of this research is to analyze the legal framework of foreign investments in public activities in light of the guidelines of the international organizations OECD - Organization for Economic Cooperation and Development and WTO - World Trade Organization. It starts from the premise that collective needs are increasingly comprehensive and that there is a deficit in their adequate fulfillment by developing countries. In parallel with this historical scenario of resources scarcity, there is a recent fiscal adjustment policy that reduces discretionary expenses. This is the case in Brazil, by Constitutional Amendment No. 95/16, known as the “Cost of Expenses”. From this perspective, policies to contain public investments are designed and private investments are stimulated, including those from foreign sources. The scenario encourages various financial and legal arrangements containing external resources to support the provision of services that meet collective needs, acquiring different forms such as Foreign Direct Investment, loans, public concessions or public services. Unlike the legal treatment of other legal systems in the world, there is no legal compilation of the Brazilian regime for foreign investment but is provided in a diffuse way throughout the Brazilian legal framework. Law No. 4,131/62 is the main source of foreign investment treatment, which is not exactly a Legal Framework or a The statute, according to the logic of contemporary legislation, as it only refers to registrations, tax, and operational aspects, without going into relevant topics such as possible sectorial prohibitions, incentive policies, dispute resolution in case of transnationality involving the Public Administration etc. Considering that Brazil has signaled its interest in becoming a member of the Organization for Economic Cooperation and Development (OECD) and the intention to adhere to the Government Procurement Agreement of the World Trade Organization (WTO), this is an opportune moment to revisit the national legislative panorama, in order to assess the compatibility with the regulatory standards of the main international organizations that deal with economic issues. The research starts from the problematic posed to, using the methodology of literature review and legislative analysis, design the current legal regime of foreign investments in the legal system. To achieve the research objective, however, the study answers some preliminary issues about the concept of foreign investment as an economic category; the relationship between private foreign investments and public investments to meet collective needs and their legal natures; the constitutional legitimacy to deal with the issue and the compatibility of the constitutional amendments opening to foreign capital, listing sectorial restrictions, to clarify the domestic legal regime. Based on this premise, binding and non-binding OECD instruments that have not yet been internalized in the country were researched. Regarding the WTO, the Public Procurement Agreement was analyzed, which aims to expand the participation of foreign companies in bids held in Brazil. The thesis concluded that, in general, national legislation meets the general premises intended by international organizations, but actions are required as knowledge and acculturation on the subject and this work contributes to that goal